2019
DOI: 10.14710/buloma.v9i1.23363
|View full text |Cite
|
Sign up to set email alerts
|

Kondisi Hidrooseanografi Muara Sungai Jelitik, Sungailiat, Bangka Provinsi Bangka Belitung

Abstract: Muara Sungai Jelitik di Sungailiat Bangka merupakan alur pelayaran bagi banyak jenis kapal karena di muara ini terdapat Pelabuhan Perikanan (PPN) Sungailiat.Sedimentasi yang terjadi di muara Sungai Jelitik sangat merugikan, karena ketika air laut surut terendah muara ini tertutup sehingga mengganggu kelancaran lalu lintas kapal dari air kantong ke laut bebas maupun sebaliknya.Pantai Pulau Bangka adalah pantai yang mempunyai arus gelombang dan angkutan sedimen sejajar pantai cukup besar yang dipengaruhi oleh ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…The Tanjung Pesona and Tanjung Tinggi observation stations have tides of 2.25 m and 1.9 m, respectively. The results of determining the type of tide are following previous studies (Pamungkas, 2018;Radjawane et al, 2018;and Wiguna et al, 2020), which found a single daily (diurnal) tidal type pattern in the waters of Bangka and Belitung.…”
Section: Tidal Characteristics and Dynamicssupporting
confidence: 76%
“…The Tanjung Pesona and Tanjung Tinggi observation stations have tides of 2.25 m and 1.9 m, respectively. The results of determining the type of tide are following previous studies (Pamungkas, 2018;Radjawane et al, 2018;and Wiguna et al, 2020), which found a single daily (diurnal) tidal type pattern in the waters of Bangka and Belitung.…”
Section: Tidal Characteristics and Dynamicssupporting
confidence: 76%
“…Harmonic analysis of the recorded data is carried out to obtain important water level elevation values such as Highest High Water Level, Mean Higher High Water, Mean Lower High Water, Mean Higher Low Water, Mean Lower Low Water, and Lowest Low Water Level, the results of the analysis are tidal constants tides used in calculating the critical elevations of tides in rivers (Wiguna et al, 2020).…”
Section: Tidal Data Validationmentioning
confidence: 99%
“…Currents in the river channel are strongly influenced by the ebb and flow of seawater, where when the tide goes upstream and vice versa when it recedes, the current direction goes downstream (Wiguna et al, 2020). Validation of ocean currents data from hydrodynamic modeling with MIKE 21 was also carried out on field ocean currents data.…”
Section: Ocean Current Data Validationmentioning
confidence: 99%
“…Hal tersebut terjadi juga di daerah aliran Sungai Jelitik di Kec Sungailiat. Sedimentasi di muara S Jelitik tergolong sangat parah sehingga ketika air laut surut, kapal-kapal tidak dapat keluar masuk ke Pelabuhan Perikanan Nusantara (PPN) Sungailiat (Wiguna et al, 2020;Wibowo dan Rachman, 2020). Permasalahan ini sudah berlangsung sejak tahun 2004 atau sudah berlangsung selama 14 tahun yang lau.…”
Section: Latar Belakangunclassified